2011
DOI: 10.1055/s-0030-1270467
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between IL-18 Serum Levels and the Prevalence of Metabolic Syndrome in Polish Men Over the Age of 40 According to Other Selected Inflammatory Indices and Androgens: Comparison of NCEP with IDF Criteria

Abstract: Inflammatory parameters were better than a deficit of androgens in identifying men suffering from MS. However, the best correlation with the number of MS components was revealed by IL-18 plasma levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…We have also previously demonstrated that even when matched for IR, women with PCOS had greater VLDL levels, small dense LDL and reduced high‐molecular‐weight adiponectin . There is some evidence that hyperandrogenaemia contributes to a pro‐inflammatory state, but this is not consistent . There is also evidence that elevated triglyceride and low HDL levels are associated with increased WCC and in vitro models have demonstrated triglyceride mediated activation of neutrophils .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We have also previously demonstrated that even when matched for IR, women with PCOS had greater VLDL levels, small dense LDL and reduced high‐molecular‐weight adiponectin . There is some evidence that hyperandrogenaemia contributes to a pro‐inflammatory state, but this is not consistent . There is also evidence that elevated triglyceride and low HDL levels are associated with increased WCC and in vitro models have demonstrated triglyceride mediated activation of neutrophils .…”
Section: Discussionmentioning
confidence: 96%
“…20,21 There is some evidence that hyperandrogenaemia contributes to a pro-inflammatory state, but this is not consistent. 17,18 There is also evidence that elevated triglyceride and low HDL levels are associated with increased WCC and in vitro models have demonstrated triglyceride mediated activation of neutrophils. 33 Thus, it is plausible that hyperandrogenaemia, central adiposity and dyslipidaemia individually or in combination might explain leucocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several pieces of evidence that hyperandrogenism contributes to a pro-inflammatory state, but they are not consistent [16,17]. The expression pattern of androgen receptors, which have been documented in lymphoid and nonlymphoid cells of thymus and bone marrow but not in mature peripheral lymphocytes, suggests that androgen plays an important part in the development and activation of lymphocytes [18].…”
Section: Commentsmentioning
confidence: 99%
“…SHBG also affects inflammatory pathways by interacting with lymphocytes via membrane receptors 53. CRP shows no direct association with androgens, both gonadal and adrenal, implying that SHBG changes might happen prior to changes in androgens, suggesting even more the important role of early SHBG imbalance in MS. Our current and earlier research suggests that the consequence of chronic inflammation in patients with metabolic syndrome might be more complicated, affecting hormones and their carrier proteins as well 54…”
Section: Discussionmentioning
confidence: 72%